G-20 Modi's idea of peace for Russia- Ukrain war - Bahuguna, Rohit (New Delhi Surendra Publications, 2023)
About G-20 Modi's Idea of Peace For Russia- Ukrain War.
Keywords: Foreign policy; International War; G-20 Summit